SFlt-1 and IP-10 in women with early-onset preeclampsia - Oliveira, Leandro Gustavo de [UNESP]; Câmara, Niels Olsen S.; Peraçoli, José Carlos [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP]; Moron, Antonio F.; Sass, Nelson (Elsevier, 2011)
Intense inflammatory response and an anti-angiogenic state have been implicated in the pathogenesis of preeclampsia. Here, we investigated this hypothesis evaluating the serum concentrations of CXCL10/IP-10, sFlt-1, and PlGF in women with early-onset preeclampsia. CXCL10/IP-10 was measured by Cytometric Bead Array. sFlt-1 and PlGF were measured by automated electrochemiluminescence immunoassay. The median serum concentration of CXCL10/IP-10 was 109.5 pg/mL in preeclamptic women, as compared with 52.28 pg/mL in the controls (P = 0.0028). The mean serum level of sFlt-1 was 13,636 pg/mL in preeclamptic women, as compared with 2020 pg/mL in the controls (P < 0.0001). PlGF levels were significantly lower in women with preeclampsia. © 2011 International Society for the Study of Hypertension in Pregnancy. Published by Elsevier B.V. All rights reserved.
Keywords: Angiogenic factors; Inflammation; IP-10; PlGF; Preeclampsia; sFlt-1; gamma interferon inducible protein 10; placental growth factor; vasculotropin receptor 1; adult; chemoluminescence; clinical article; controlled study; cytometry; female; human; hypothesis; immunoassay; inflammation; pathogenesis; preeclampsia; protein blood level